Health and economic impact of caregiving on informal caregivers of people with chronic diseases in sub-Saharan Africa: A systematic review. - Ephraim Kisangala; Etheldreda Leinyuy Mbivnjo; Edward J D Webb; Barbara Barrett; Godfrey Zari Rukundo; Eve Namisango; Margaret Heslin (PLOS Global Public Health)
With a disproportionate burden of chronic diseases and severe shortage of health workers in sub-Saharan Africa, the region implicitly relies on informal caregivers (ICGs) to support the patients both within and outside the health facilities. The aim of this review is to systematically summarise evidence on the health and economic impact of caregiving on informal caregivers of patients with chronic diseases in sub-Saharan Africa. Medline (Ovid), CINAHL (EBSCOhost), PsycINFO (Ovid), Embase (Ovid), Global Health, and Web of Science databases were systematically searched to identify original articles that considered the economic and/or health impacts of caregiving in sub-Saharan Africa. The results from the included studies were synthesised narratively. After screening 4,951 records, 47 studies were included for synthesis. The articles were from all sub-regions of sub-Saharan Africa with more than half (25/47) of the studies focussing on caregivers for patients with cancer. Although the primary motivation for becoming caregivers was love and responsibility, the caring responsibilities described in twenty studies, had profound effects on the caregiver's lives. Healthwise, the informal caregivers experienced changes in their physical and mental health like developing musculoskeletal problems and depression. Economically, caregiving was expensive, and financially draining. The opportunity cost of caregiving included loss of jobs, loss of income, foregoing planned important activities and missed education opportunities. Informal caregivers reported a range of mainly negative health and economic effects of the work they do. Health care systems should consider how to better support caregivers in terms of their own physical and mental wellbeing. Also, governments should develop strategies to financially support informal caregivers.